Patogenity Of Beauveria bassiana On Compost Media For Palm Oil Pest Control Oryctes rhinoceros L - Rina Novianti; Hafiz Fauzana; Rusli Rustam (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2021)
Oryctes rhinoceros is an important pest of oil palm. This study aimed to obtain the best ability of several compost organic materials containing B. bassiana for controlling O. rhinoceros larvae, to obtain the ability of B. bassiana in compost to control various instars of O. rhinoceros larvae, and to obtain the best concentration of Beauveria bassiana in compost in controlling O larvae. rhinoceros. Three stages of the research experiment were: 1) testing of several compost organic materials containing B. bassiana at 75 gl-1 concentration, using a completely randomized design (CRD), Experiment 2 were: test the ability of B. bassiana with 75 gl-1 concentration of compost at various instars of O. rhinoceros larvae. Experiment 3 were: concentration test of B. bassiana fungi in compost media against O. rhinoceros larvae, with 6 treatments 4 replications obtained 24 experimental units, while the treatments were 0 gl-1, 15 gl-1, 30 gl-1, 45 gl-1, 60 gl-1, and 75 gl-1. Compost organic material contains the fungus B. bassiana which has the best ability to control O. rhinoceros, namely OPEFB + sawdust because caused total mortality to reach 90% with conidia number 115.2 x108, initial death 67.2 hours after application, lethal time 50 206, 4 hours after application. B. bassiana fungi in OPEFB + sawdust compost can control O. rhinoceros 3 instar larvae with total mortality of up to 92.5% and control 1, 2, and 3 instars larvae of O. rhinoceros have no effect on the initial time of death and lethal time 50 on each instar. The initial time of death used was 54-75 hours and the lethal time 50 was 198-252 hours. OPEFB compost + sawdust containing the fungus B. bassiana 75 gl-1 had the best ability to control O. rhinoceros larvae with a total larvae mortality of 87% which caused early death 54 hours after application, 50 lethal times of 213 hours, and LC50 of 3.3% or the equivalent of 33 gl-1.